Hidden diversity in neglected structures: A morphological study of the terminalia of Limnocoris Stål, 1860 (Hemiptera: Heteroptera: Naucoridae), with descriptions of two new species from Brazil and taxonomic notes - Rafael P. R. Canejo; Higor D. D. Rodrigues; Felipe F. F. Moreira (PLoS ONE, 2025)
Limnocoris Stål, 1860 (Hemiptera: Heteroptera: Naucoridae) occurs from the United States to Argentina and is the most speciose genus of Naucoridae, with 75 valid species. Four taxonomic revisions were recently published, which facilitates the identification of described species and the discovery of new ones. Nonetheless, the female terminalia of the genus remains mostly unknown and the male genital capsule has been often ignored due to its uniformity among species. This study aims to fill this gap by providing descriptions and photographs of the female terminalia and male genital capsule for 28 species from Brazil, including two that are described here: L. curvipenis n. sp. and L. sitesi n. sp. Both of them display diagnostic characters in the female terminalia, and a distinct male phallosoma is herein recorded for the first time in the genus. The following new synonymies are proposed: Limnocoris intermedius Nieser & Lopez-Ruf n. syn. and L. lanemeloi Nieser & Lopez-Ruf n. syn. as junior synonyms of L. decarloi Nieser & Lopez-Ruf, and L. nigropunctatus Montandon n. syn. as junior synonym of L. pauper Montandon. The following species are resurrected from synonymy and their species status are restored: Limnocoris admontandoni La Rivers stat. restit. from synonymy with L. insignis Stål, and L. sattleri De Carlo stat. restit. from synonymy with L. nigropunctatus. Our work reveals a notable diversity in the female terminalia of the taxa examined and provides a basis for future taxonomic and systematic studies on this and other genera of Naucoridae.